As estratégias da logística contemporânea como instrumento de ordenamento territorial na reconversão em Nord e Pas-de-Calais (França) - Mauricio Aquilante Policarpo; Rita de Cássia Martins de Souza (Confins, 2019)
This article discusses the capitalist actions in the French departments – Nord and Pas de Calais, in the Hauts de France region, in the face of the process of Territorial Reconversion process after the years of 1960. Reconversion, as a geostrategy, seeks to change the expertise of the area from the crisis of the traditional industries (coal mining and textiles) and the consequent problem of unemployment and economic atony. Thus, since the 1960s, important infrastructure has been installed in the region by the French State and by the European Union in association with private capital actions in order to attract modern economic activities and innovation. The geographical situation of Nord and Pas-de-Calais fulfills a decisive role in the successive investments in the area as it is located in an essential border area in the context of the European Union. It is of fundamental importance to understand the strategies of contemporary logistics in the articulation of Nord and Pas-de-Calais as nodes of the European transport network, in which the interests of local, national and global economic agents collide.